Modification of endurance wave analysis based on New-wave theory. (3rd April 2017) - Mohajernassab, Saeed; Diznab, Mohammad Ali Dastan; Mehdigholi, Hamid; Seif, Mohammad Saeed; Tabeshpour, Mohammad Reza
Abstract : The main objective of this investigation is to modify endurance wave analysis (EWA) based on New-wave theory for convenient assessment of offshore structures under extreme waves. EWA is a novel time history based approach to evaluate structural performance in various excitation levels of wave loading by intensifying wave records. In this article, modifications are proposed to determine appropriate time duration and intensifying trend for reliable and practical assessment of offshore structures. In this way, a simplified model of a real jacket platform is utilised to investigate the application of this approach under extreme wave conditions in the Persian Gulf and results are compared with typical three hour random wave simulations. It is shown that in extreme waves, except resonance states, proposed method can estimate the structural response with acceptable accuracy and very low computational costs.